2013
DOI: 10.1530/rep-13-0244
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-linolenic acid from flaxseed oil improved folliculogenesis and IVF performance in dairy cows, similar to eicosapentaenoic and docosahexaenoic acids from fish oil

Abstract: The objectives of this study were to determine the differential incorporation of various omega-3 (n-3) fatty acids (FAs) supplemented to dairy cows into ovarian compartments and assess the effects on IVF. Forty-two 256-day pregnant cows were supplemented with encapsulated fats, in treatments designated as i) SFA -saturated fat at 240 and 560 g/day per cow, prepartum and post partum (PP) respectively; ii) FLX -flaxseed oil at 300 and 700 g/day per cow prepartum and PP respectively; and iii) FO -fish oil at 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 37 publications
7
81
0
3
Order By: Relevance
“…Nevertheless, results from feeding linseeds on reproductive variables are inconsistent. Some authors reported an improved increased follicular and corpus luteum growth , oocyte (Moallem et al, 2013;Zachut et al, 2010) and embryo quality (Thangavelu et al, 2007), decreased pregnancy loss (Ambrose et al, 2006), reduced plasma prostaglandin (Petit et al, 2002), and increased serum progesterone concentration (Jahani-Moghadam et al, 2015), reduced interval from calving to ovulation (Colazo et al, 2009). In contrast, others noted no changes in milk progesterone concentration or corpus luteum activity (Ponter et al, 2006), or oocyte quality (Bilby et al, 2006, Fouladi-Nashta et al, 2009.…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 99%
“…Nevertheless, results from feeding linseeds on reproductive variables are inconsistent. Some authors reported an improved increased follicular and corpus luteum growth , oocyte (Moallem et al, 2013;Zachut et al, 2010) and embryo quality (Thangavelu et al, 2007), decreased pregnancy loss (Ambrose et al, 2006), reduced plasma prostaglandin (Petit et al, 2002), and increased serum progesterone concentration (Jahani-Moghadam et al, 2015), reduced interval from calving to ovulation (Colazo et al, 2009). In contrast, others noted no changes in milk progesterone concentration or corpus luteum activity (Ponter et al, 2006), or oocyte quality (Bilby et al, 2006, Fouladi-Nashta et al, 2009.…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 99%
“…Evans et al (28) and Mossa et al (29) confirmed that application of n-3 fatty acids causes an increase in folliculogenesis by increasing the number and size of oocytes during the estrous cycle, which positively affects the performance of dairy cattle fertility. The presence of n-3 fatty acids in the diet causes a change in the fatty acid profile in the cumulus-oocyte complexes (COCs), in a similar manner as in the follicular fluid and granulosa cells (27). The diet used in these studies contained flaxseed oil and fish oil.…”
Section: Effect Of Fish Oil On Cow Reproductionmentioning
confidence: 99%
“…Changing the serum lipid profile can change lipid availability in the ovarian follicle and affect embryogenesis after fertilization (Johnson and Nasr-Esfahani, 1994). Dietary fatty acids can enhance oocyte maturation and quality (Moallem et al, 2013). But excess circulating lipids and excess amounts of non-esterified fatty acids can increase ROS and negatively affect oocyte quality and embryo development (Leroy et al, 2005; Shehab-El-Deen et al, 2009).…”
Section: Activation and Inhibition Of Er Stress In Oocytes And Embmentioning
confidence: 99%